Optimalisasi Pemasaran dan Produksi Kopi Tangsi Wangi melalui Digital Marketing dan Edukasi Petani - Erpurini, Wala; Leonandri, Dino Gustaf; Alamsyah, Nur (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The community engagement program aims to optimize the marketing and production of Tangsi Wangi Coffee through the implementation of digital marketing and farmer education in the region. Tangsi Wangi Coffee, as a prominent local product, holds significant potential for further development in the global market. However, limited knowledge of digital marketing strategies and efficient production techniques poses major challenges for local coffee farmers. Therefore, this program focuses on two key aspects: first, providing training for farmers on improved and sustainable coffee cultivation techniques; and second, enhancing marketing capacities by introducing them to digital marketing concepts, including the use of social media, e-commerce, and other online marketing platforms. This initiative is expected to boost the competitiveness of Tangsi Wangi Coffee in local and international markets while positively impacting farmers' welfare by increasing income and expanding market access. Beyond improving farmers' skills in production and marketing, the program aims to create greater added value for the local community and strengthen the global competitiveness of Tangsi Wangi Coffee. Additionally, it seeks to establish a mutually beneficial ecosystem among farmers, coffee entrepreneurs, and consumers.